China’s Political Worldview and Chinese Exceptionalism: A Book Review - Isti Nur Rahmahwati (Indonesian Perspective, 2025)
This fascinating book is a product of Benjamin Ho’s PhD dissertation, examining an interpretative concept of exceptionalism distinct from the Western idea. It presents a systematic and well-constructed analysis of how the rise of China as an emerging global power and its international political perspective is being comprehensively interpreted through Chinese exceptionalism discourse. The comparison of four Chinese IR thoughts and mainstream IR theories derived from realism, liberalism, and constructivism presents multiple views to understand the study of China’s international relations. Through his study, Ho unravels China’s exceptionalism in perceiving itself as different and unique in conducting international relations, particularly after President Xi Jinping took office in 2012. Ho further identifies how it influences the dynamics of China’s political actions in the existing international order and the possibility of China’s attempts to establish its preferred world order vis-à-vis the Western-led. A well-combined elaboration of historical, domestic political, cultural value, and sociological factors provides more inclusive outlooks determining the motivation and the way Chinese leaders and policymakers think about and propose expansive strategies to promote Beijing’s norms and objectives to the international realm.